1990
DOI: 10.1111/j.1745-459x.1990.tb00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of External Fat Cover, Bone Removal and Endpoint Cooking Temperature on Sensory Attributes and Composition of Pork Center Loin Chops and Roasts

Abstract: ABSTRACT. Effects of fat cover, bone removal and endpoint cooking temperature on proximate and sensory characteristics of pork center loin chops were investigated. Only brown color of broiled chops was affected by presence of bone and by endpoint temperature. Fat cover only affected perceived chewiness of chops. Broiled boneless chops contained higher percent fat than bone‐in chops. There were no differences in protein, fat or moisture percentages in cooked chops due to fat cover. Higher internal temperature d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Protein content increased significantly ( P < 0.01) as pasteurization temperature increased, which could be due to loss of moisture and fat contents of the sausages at higher reheating temperatures. Similar findings were also reported in pork loin chops (Siemens et al. 1990).…”
Section: Resultssupporting
confidence: 90%
“…Protein content increased significantly ( P < 0.01) as pasteurization temperature increased, which could be due to loss of moisture and fat contents of the sausages at higher reheating temperatures. Similar findings were also reported in pork loin chops (Siemens et al. 1990).…”
Section: Resultssupporting
confidence: 90%
“…Reports on the influence of the presence of bone and level of external fat cover on eating quality are more difficult to find, but one study does show that consumers found pork loin chops from fat carcasses (15.5-16.6 mm mean fat thickness measurements over longissimus dorsi at the last rib) more juicy and tender than those from lean carcasses (8.4 to 8.8 mm; Kempster, Dilworth, Evans, & Fisher, 1986). In contrast, a taste panel found that broiled loin chops with a fat cover of 6 mm were chewier than chops with no fat cover and that consumers preferred trim loin roasts to those with 6 mm fat cover (Siemens, et al, 1990). These workers also found that the presence of the bone did not influence the degree of liking of the pork roasts.…”
Section: Discussionmentioning
confidence: 99%
“…The number of points along an intensity scale is determined according to the degree of product differences. Many researchers have used a nine point scale(Heymann et al, 1990;Siemens et al, 1990;Dikeman, 1987; Murphy and Carlin, 1960, and others). The ends of the scale with this many points are rarely if ever used (as seen by ranges) unless many differences exist between samples.…”
mentioning
confidence: 99%